Evaluation of the management system and proposal of Balanced Scorecard in a higher educational institution - Santisteban Salazar, Mirtha Yvis (2020)
The adoption of appropriate strategic management models in higher education institutions is necessary. The objective was to evaluate the management and propose a strategic management model based on the balanced scorecard in a public institution of higher education in Bagua Grande. Observational, descriptive, intentional and cross-sectional study, carried out in 2012. The sample consisted of 5 managers, 7 administrators and 15 teachers, intentionally selected. Institutional management was evaluated by SWOT analysis and surveys of managers, administrators and teachers validated by Cronbach's alpha. 100% of the managers surveyed indicated an unequal distribution of resources between areas, ignorance of financial goals, inadequate management style; administrative officials indicated ignorance of objectives or goals in their area (85.7%), lack of leadership (71.4%), disinterest in occupational hygiene (71.4%); while teachers mentioned an inappropriate relationship between managers (66.7%), inadequate planning and organization of teamwork (53.3%), lack of concern for the needs of students (53.3%). It is concluded that the evaluation detected staff dissatisfaction in relation to the management system and the proposed balanced scorecard allowed defining the objectives, indicators and strategic goals for each perspective with an adequate alignment with the institutional mission and vision, which would result in an improvement of the strategic management of this institution.